Control of VSC‐HVDC connected wind farms for system frequency support. (1st March 2020) - Guo, Xiaolong; Yan, Jiaming; Xu, Guoyi; Hu, Jiaxin; Bi, Tianshu
Summary: With the increasing offshore wind farms connected into large power grid by VSC‐HVDC, the system equivalent inertia has been further reduced, which has brought new challenges to the safe operation of the system. In this article, we proposed a novel strategy to coordinate the rotational kinetic energy of variable speed wind turbines and the capacitor energy of VSC‐HVDC to support the main power system frequency. Selection of controller parameters is discussed to improve the frequency control effect. This strategy reduces the rate of change of frequency and improves the frequency nadir, which also limit the wind turbine rotor speed variation range to maintain its stable operation. The proposed strategy can also reduce the secondary frequency drop to a large extent. The proposed strategy is verified by using a power system model in MATLAB/Simulink. The simulation results show that the proposed method can effectively utilize the frequency control capability of VSC‐HVDC and the wind farm to maintain frequency stability of the power system.